Considerations on the potential for obtaining biogas from biomass by anaerobic digestion - Iuliana Găgeanu; Ana-Maria Tăbăraşu; Cătălin Persu; Dan Cujbescu; Gabriel Gheorghe (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
Some of the main environmental problems of today's society are the continuous increase of the amount of organic residues and the consumption of conventional (non-renewable) energy. One way to address these issues is through the processing of this residues and the production of biogas. Anaerobic digestion is considered to be the optimal treatment for various types of agricultural and wood biomass and for a wide variety of organic residues suitable for this purpose, these substrates being thus transformed into recoverable energy and organic fertilizer for agriculture. Anaerobic digestion is a microbiological process of decomposition of organic matter, in the absence of oxygen, applied on a large scale for the production of renewable energy. The paper presents a series of considerations on obtaining biogas through anaerobic digestion from agricultural biomass, wood, energy crops and food waste.
Keywords: Q10; 330; biomass; biogas; anaerobic digestion; methanogenesis